224 "OLDER PEOPLE WANT TO BE IN THEIR OWN HOMES": THEMATIC ANALYSIS- PATIENT AND CARER FEEDBACK AFTER PATHFINDER EMERGENCY CALL RESPONSE. (25th October 2022) - Bernard, P; Corcoran, G; O'Brien, C; Ward, P; Kenna, L; Laura, H; Mooney, R; Howard, W; Horgan, F; Malone, A; Masterson, S
Abstract: Background: Older adults are frequent attendees at the Emergency Department (ED) and experience high rates of adverse outcomes following ED presentation. There is a growing evidence base for alternative care pathway models at the time of a low acuity emergency medical services (EMS) call. Previous research has found a high level of patient satisfaction with the Pathfinder model, in which an Advanced Paramedic and a Physiotherapist or Occupational Therapist respond to EMS calls [1]. However, the reasons underpinning this from a patient perspective have not previously been reported. Methods: This is a qualitative study employing thematic analysis of open-ended responses recorded in 429 telephone interviews with service users (patients or their next-of-kin), who had been attended by the Pathfinder service following an EMS call. Results: Five primary themes were identified: (1) the professionalism of the interdisciplinary clinical team; (2) "the right service, in the right place at the right time"; (3) the role of Pathfinder in "getting the ball rolling" through following up and co-ordinating referrals and services; (4) the lasting impact of the experience on the patient and their next-of-kin; (5) the value of skilled communication with the older person, as well as smooth and "tuned-in" communication across the team. Conclusion: Older people voiced a clear preference for hospital avoidance, and strongly valued the opportunity to be assessed and treated in their homes at the time of an EMS call rather than automatic conveyance to the ED. They recognised the value of a skilled interdisciplinary team, with a follow-up service, that effectively positions itself between the acute hospital and community services. Reference: 1. Bernard P, Corcoran G, Kenna L, et al. Is Pathfinder a safe alternative to the emergency department for older patients? An observational analysis. Age Ageing 2021; 50(5):1854–1858.